Novel Glycoconjugate of 8-Fluoro Norfloxacin Derivatives as Gentamicin-resistant Staphylococcus aureus Inhibitors: Synthesis and Molecular Modelling Studies - Azad, Chandra S.; Bhunia, Shome S.; Krishna, Atul; Shukla, Praveen K.; Saxena, Anil K. (Chemical biology & drug design, 2015)
Antibiotic resistance has been the subject of interest in clinical practice due to high prevalence of antibiotic‐resistant pathogenic organisms. In view of the prevalence of lesser resistance in antibiotics belonging to aminoglycoside class of compounds viz. Food and Drug Administration‐approved gentamicin for the treatment of Staphylococcus infections, which also has instances of resistance in the clinical isolates of Staphylococcus aureus, a series of novel glycoconjugates of 8‐fluoro norfloxacin analogues with high regio‐selectivity by employing copper (I)‐catalyzed 1, 3‐dipolar cycloaddition of 1‐O‐propargyl monosaccharides has been synthesized and evaluated for the antibacterial activity against gentamicin resistance Staphylococcus aureus. Among these compounds, the compound 10g showed better antibacterial activity (MIC = 3.12 μg/ml) than gentamicin (Escherichia coli (12.5 μg/ml), Staphylococcus aureus (6.25 μg/ml) and Klebsiella pneumonia (6.25 μg/ml), including gentamicin resistant (>50 μg/ml) strain in vitro). The docking studies suggest DNA gyrase of Staphylococcus aureus as a probable target for the antibacterial action of compound 10g. In order to combat gentamicin resistance caused by reduced cell wall permeability, the glycoconjugates of norfloxacin have been synthesized that displayed excellent antibacterial activity as compared to gentamicin.